A High‐Performance Nonfused Wide‐Bandgap Acceptor for Versatile Photovoltaic Applications. Issue 5 (17th December 2021) - Bi, Pengqing; Zhang, Shaoqing; Ren, Junzhen; Chen, Zhihao; Zheng, Zhong; Cui, Yong; Wang, Jianqiu; Wang, Shijie; Zhang, Tao; Li, Jiayao; Xu, Ye; Qin, Jinzhao; et al.
Abstract: Wide‐bandgap (WBG) nonfullerene acceptors (NFAs) with nonfused conjugated structures play a critical role in organic photovoltaic (OPV) cells. Here, NFAs named GS‐OEH, GS‐OC6, and GS‐ISO, with optical bandgaps larger than 1.70 eV, are synthesized without using the fused ring structures. Compared with GS‐OEH and GS‐OC6, GS‐ISO exhibits much stronger crystallinity, leading to a smaller energetic disorder and a larger exciton diffusion coefficient. GS‐ISO also possesses a higher electroluminescence external quantum efficiency of 1.0 × 10 −2 . The OPV cell based on PBDB‐TF:GS‐ISO demonstrates a power conversion efficiency (PCE) of 11.62% under the standard one sun illumination. Besides, the PBDB‐TF:GS‐ISO‐based cell with effective area of 1.0 cm 2  exhibits a PCE of 28.37% under 2700 K illumination of 500 lux. A tandem OPV cell using PBDB‐TF:GS‐ISO as the front subcell shows an outstanding efficiency of 19.10%. Importantly, the GS‐ISO‐based OPV cell exhibits promising stability under the continuous illumination of simulated sunlight. This study indicates that the molecular design strategy demonstrated in this work has great superiority in developing nonfused NFAs and also that GS‐ISO is a promising WBG acceptor for versatile photovoltaic applications. Abstract : A new wide‐bandgap nonfused nonfullerene acceptor named GS‐ISO is designed and synthesized. GS‐ISO exhibits a very flat molecular backbone and stable molecular conformation. Based on GS‐ISO, outstanding power conversion efficiencies of over 19% (AM 1.5G, 100 mW cm −2 ) for a tandem organic photovoltaic (OPV) cell and over 28% (500 lux, 2700 K LED) for an indoor OPV cell are achieved.